Fulfilment in Matthew - Viljoen, Francois P. (Verbum et ecclesia, 2007)
Matthew extensively explored the motif that Jesus was the fulfilment of the Old Testament hopes. In this article investigation is done on the way Matthew employs this motif. The expression of fulfilment of Scripture had an important function in early Christian circles. The Christian faith had to be legitimatized by reference to the Jewish Scriptures. What happened to Jesus and the rise of the Christian church were to be identified as the fulfilment of the promises of the Old Testament. For today’s reader it seems as if Matthew sometimes draws awkward links between Old Testament citations and their fulfilment in Jesus. However, when his hermeneutical method is being mirrored against contemporary interpretative methods, it becomes clear that Matthew used the fulfilment motif in a then acceptable way to strategically and persuasively place Jesus’ ministry within the unfolding plan of God.